ANALISIS INTERAKSI SOSIAL SISWA TUNA RUNGU DI SEKOLAH ‘AISYIYAH BUSTANUL ATHFAL - Terza Travelancya (Alzam: Journal of Islamic Early Childhood Education, 2022)
Abstract: This study aims to determine the social interaction of deaf students with regular students, classroom teachers, special supervisors and to know the strategy of fostering deaf students in the development of social interactions. The method used in this study is a qualitative descriptive method. The subjects in this study were one special supervising teacher (GPK), one class teacher, one student guardian and one deaf child in 'aisyiyah bustanul athfal. Data collection techniques using interviews, observation and documentation. This study describes social interactions between deaf students and regular students, namely by using local sign language, having imitation or imitating behavior, associative behavior such as cooperating and having a sense of concern for friends, and dissociative behavior that is sensitive and difficult to control emotions when regular students disturb them. The interaction of deaf students with teachers uses local and national sign languages, the teacher provides a positive stimulus so that the nature of suggestions and feelings of comfort appear when together with the teacher. Strategies for fostering deaf students in the development of social interactions by developing skills using lip language and sign language as well as emotion regulation.